A coarse grained molecular dynamics simulation study on the structural properties of carbon nanotube–dendrimer composites. Issue 16 (10th April 2018) - Kavyani, Sajjad; Dadvar, Mitra; Modarress, Hamid; Amjad-Iranagh, Sepideh
Abstract : By coarse grained molecular dynamics, the effect of the size and hydrophilic/hydrophobic properties of the interior/exterior structures of the dendrimers in carbon nanotube–dendrimer composites has been studied, to find a stable composite with the capability to be used in drug delivery. Abstract : By employing coarse grained (CG) molecular dynamics (MD) simulation, the effect of the size and hydrophilic/hydrophobic properties of the interior/exterior structures of the dendrimers in carbon nanotube (CNT)–dendrimer composites has been studied, to find a stable composite with high solubility in water and the capability to be used in drug delivery applications. For this purpose, composites consisting of core–shell dendrimer complexes including: [PPIcore–PAMAMshell], [PAMAMcore–polyethyleneglycol (PEG){shell}] and [PAMAMcore–fattyacid (FTA){shell}] were constructed. A new CG model for the fatty acid (FTA) molecules as functionalized to the dendrimer was developed, which, unlike the previous models, could generate the structural conformations of the FTA properly. The obtained results indicated that the dendrimer complexes with short FTA chains can form stable composites with the CNT. Also, it was found that the pristine PAMAM and PPI–PAMAM with small PPI, and PAMAM–PEG dendrimers with short PEG chains, can distribute their chains into the water medium and interact with the CNT efficiently, to form a stable water-soluble CNT–dendrimer composite. The results demonstrated that the structural difference between the interior and exterior of a core–shell dendrimer complex can prevent the core and the interior layers of the dendrimer complex from interacting with the CNT. An overall analysis of the results manifested that the CNT–PAMAM:4–PEG:4 is the most stable composite, due to strong binding of the dendrimer with the CNT while also having high solubility in water, and its core retains its structure properly and unchanged, suitable for encapsulating drugs in the targeted delivery applications.